2022
DOI: 10.3390/educsci12100702
|View full text |Cite
|
Sign up to set email alerts
|

Towards Digitalization in Early Childhood Education: Pre-Service Teachers’ Acceptance of Using Digital Storytelling, Comics, and Infographics in Saudi Arabia

Abstract: Despite the promise of digital technology to enhance the teaching–learning process, integrating it into early childhood education remains a challenge. Recent literature shows that novice teachers do not fully utilize the potential of digital technology to promote student learning. Therefore, this study aims to investigate early childhood pre-service teachers’ intentions to use three digital technology applications—Digital storytelling, digital comics, and digital infographics—As teaching tools, which criticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…Several researches highlighted the need for teachers to be equipped to employ a range of digital technology applications to improve young children's learning at home and in school (Al-Abdullatif, 2022). Teachers lack the su cient background to design, develop and employ digital technologies in their classes (Bugis, 2018;Al-abdullatif, 2022).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Several researches highlighted the need for teachers to be equipped to employ a range of digital technology applications to improve young children's learning at home and in school (Al-Abdullatif, 2022). Teachers lack the su cient background to design, develop and employ digital technologies in their classes (Bugis, 2018;Al-abdullatif, 2022).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…The issues of how children acquire literacy skills, the importance of the literacy classroom environment, and teachers' practices are already topics covered in a large body of literature [3,[5][6][7][8]. A study by Hofslundsengen et al [9] noted that the physical environment of literacy classrooms and its components in Scandinavia can affect children's acquisition of literacy skills.…”
Section: Introductionmentioning
confidence: 99%
“…Aumgri and Apirating [37] concluded that digital storytelling impacts Thai students' digital skills. Moreover, Al-Abdullatif [38] highlighted the importance of digital storytelling in the education system of Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%